Two decades of herbicide-tolerant crops in the Republic of Serbia - Malidža, Goran; Jocić, Siniša; Bekavac, Goran; Krstić, Jovana; Miklič, Vladimir; Dušanić, Nenad (Acta herbologica, 2023)
Breeding of herbicide-tolerant crops in Serbia has been going on for almost three decades, and the tradition of growing it for two decades. In Serbia it is allowed to grow crops tolerant to certain herbicides that have been obtained by classic breeding methods without the use of genetic engineering. These are sunflower, oilseed rape and sugar beet tolerant to some ALS inhibitors, and maize tolerant to cycloxydim. With the exception of sunflower tolerant to tribenuron-methyl and imidazolinones, which occupies over 80% of the area under this crop in the Republic of Serbia, other herbicide-tolerant crops are represented on smaller areas (1-17%). The potential of these crops is often not used in the best way, and the main challenge and threat are weeds resistant to herbicides to which these crops are tolerant. A big problem for the sustainability of growing these crops in Serbia is that the growers of these crops rely mainly on herbicides to which they are tolerant, neglecting other measures in integrated weed control. In order to preserve these resources as part of an integrated weed management, it is necessary to improve the level of knowledge of producers about the best practices of growing these crops, their advantages and risks. As a double-edged sword, herbicide-tolerant crops allow farmers to improve the rotation of herbicides with different mechanisms of action and the control of certain herbicide-resistant weeds, but they can also lead to overuse of herbicides to which they are tolerant and influence the selection of resistant weeds and shift of weed flora. flora. Herbicides and herbicide-tolerant crops are very important resources of modern crop production, but only as part of integrated weed managament and without excessive reliance on these crops and herbicides to which they are tolerant.